The relationship between investment and internal cash flows in VC-backed SMEs: Does firm size matter? - Zélia Serrasqueiro; Filipe Sardo; Elisabete Gomes Santana Félix (The Journal of Entrepreneurial Finance (JEF), 2019)
Using panel data models and two research sub-samples composed of smaller and larger VC-backed, this study seeks to analyze the relationship between investment and internal cash flows. The results indicate that the investment sensitivity to internal cash flows is greater in larger than in the smaller VC-backed SMEs. Debt is more important for smaller than for larger VC-backed SME investment. The moderation effect of VC ownership reduces the magnitudes of the positive impact of cash flows and debt as well as the negative effect of growth opportunities on investment in both smaller and larger VC-backed SMEs.
Keywords: C33; G23; G24; G32; 650; Internal cash flows; Debt; Growth Opportunities; Investment in Fixed Assets; SMEs; Venture Capital